Consentimento informado das pessoas com transtornos e deficiências mentais à luz do Estatuto da Pessoa com Deficiência: diálogos hermenêuticos na relação médico-paciente - Tiago Vieira Bomtempo (2021)
Law no. 13.146 / 2015, known as the Disabled Person Statute, changed significantly the disability regime in the Civil Code of 2002. Among its amendments, those who, due to illness or mental disability, do not have the necessary discernment for the practice, are no longer absolutely incapable of the acts of civil life, and those with reduced discernment and exceptional ones without complete mental development are no longer considered relatively incapable. Thus, the previous legal criterion for the protection of the vulnerable, such as people with mental disorders and disabilities, passes to the promotion of the exercise of their autonomy, such as the mandatory prior, free and informed consent of the disabled person to undergo treatment, procedure, hospitalization and scientific research. In this context, this research must demonstrate the effectiveness of free and informed consent (CLE) for patients with neurocognitive and psychiatric impairment, now considered capable with the wording of the aforementioned law. For this purpose, it will be used based on field research and phenomenological hermeneutics, supported by bioethics, if in practice it is possible to exercise the autonomy of these individuals in the relationship between doctor and patient. Initially, the legal capacity regime in Brazil and other countries of latin origin will be addressed; then, the understanding of the different sciences about mental disabilities and diseases; to then discuss autonomy and the term consent and its application today; at the end, bring analysis of field research, focusing on phenomenological hermeneutics, especially with language; and present criticisms and possible paths with this law. It is concluded, in principle, that it is necessary to talk about the Law with other sciences, in order to overcome the barriers of prejudice in relation to people with mental disorders and disabilities, and that there is an intense reformulation in the treatment of the doctor with the patient, so that he may be an agent of his will when discernment is possible. After all, a law does not resolve someone's autonomy in the face of countless pathologies and deficiencies that each person may present, so it is only possible to define it based on the phenomenological reduction in the specific case.